Pioneers in microbiology the human side of science - Chung, King-Thom; Liu, Jong-Kang (New Jersey World Scientific, 2018)
"Pasteurization, penicillin, Koch's postulates, and gene coding. These discoveries and inventions are vital yet commonplace in modern life, but were radical when first introduced to the public and academia. In this book, the life and times of leading pioneers in microbiology are discussed in vivid detail, focusing on the background of each discovery and the process in which they were developed - sometimes by accident or sheer providence."--Publisher description.
Antoine van Leeuwenhoek (1632-1723) : the first microbiologist -- Robert Hooke (1635-1703) : the first to observe the existence of microorganizmz -- LLazzaro Spallanzani (1729-1799) : fighting agains the odds -- Edward Jenner (1749-1823) : the first and greatest success of immunization -- Agostino Maria Bassi (1773-1856) : pioneer of studying contagious disease -- Gerhard Henrik Armauer Hansen (1841-1912) : pioneer of leprosy studies -- Robert Koch (1843-1910) : the great medical microbiologist --Élie Metchnikoff (1845-1916) : phagocytosis and immunology ; Charles Louis Alphonse Laveran (1845-1922) : discoverer of the Malaria Parasite -- Martinus Willem Beijerinck (1851-1931) : pioneer of general microbiology -- Walter Reed (1851-1902) : yellow fever fighter -- Emile Roux (1853-1933) : diseases fighter -- Emil von Behring (1854-1917) : pioneer of serology -- Erwin F. Smith (1854-1927) : father of plant pathology -- David Bruce (1855-1931) : pioneer of veterinary microbiology -- Sergei N. Winogradsky (1856-1953) : founder of soil and general microbiology -- Kitasato Shibasaburo (1853-1931) : first to isolate Clostridium tetani and a pioneer of serology -- Theobald Smith (1859-1934) : the captain of American microbe hunters -- Alexandre Yersin (1863-1943) : pioneer plague fighter -- Albert Leon Charles Calmette (1863-1933) : antituberculousis and BCG vaccination -- Charles J. H. Nicolle (1866-1936) : pioneer of typhus studies -- Howard Taylor Ricketts (1871-1910) : pioneer of rickettsial diseases studies -- Chaim A. Weizmann (1874-1952) : pioneer of industrial microbiology and first president of Israel -- Oswald Theodore Avery (1877-1955) : microbiological genetic transmission and DNA -- Frederick Griffith (1879-1941) : dscovery of transformation -- Alexander Fleming (1881-1955) : The discovery of penicillin -- Albert Jan Kluyver (1888-1956) : unity of biochemistry and pioneer of general microbiology -- Gerhardt J. Domagk (1895-1964) : pioneer of sulfur drug chemotherapy -- Paul Henry de Kruif (1890-1971) : gas gangrene research and historian of microbiology William C. Frazier (1894-1991) : pioneer of dairy and food microbiologist -- Ira Lawrence Baldwin (1895-1999) : pioneer of agricultural microbiology and education -- Cornelis B. van Niel (1897-1985) : educator and pioneer of bacterial photosynthesis and general microbiology -- Max Theiler (1899-1972) : yellow fever vaccine developer -- René Jules Dubos (1901-1982) : pioneer of bacterial antibiotics and environmental microbiology -- Barbara McClintock (1902-1992) : pioneer of microcellular directed genetics -- George W. Beadle (1903-1989) : pioneer of biochemical genetics -- Edward Lawrie Tatum (1909-1975) : pioneer of molecular genetics -- Horace A. Barker (1907-2000) : pioneer of anaerobic metabolism -- Deam Hunter Ferris (1912-1993) : pioneer of epizoonotic studies -- Herman J. Phaff (1913-2001) : pioneer of yeast biology -- Harold Boyd Woodruff (1917-2017) : antibiotics hunter and distinguished soil microbiologist -- Ralph S. Wolfe (1921 to Present) : pioneer of biochemistry of methanogenesis -- Richard L. Crowell (1930 to Present) : cellular receptors and viral infection -- Peter Charles Doherty (1940 to Present) : pioneer of immunology.
Includes bibliographical references and indexes.
Keywords: Microbiology; Biography